2014
DOI: 10.3109/10408444.2014.934439
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of potential health risks posed by pharmaceutical, occupational and consumer exposures to metallic and nanoscale aluminum, aluminum oxides, aluminum hydroxide and its soluble salts

Abstract: Aluminum (Al) is a ubiquitous substance encountered both naturally (as the third most abundant element) and intentionally (used in water, foods, pharmaceuticals, and vaccines); it is also present in ambient and occupational airborne particulates. Existing data underscore the importance of Al physical and chemical forms in relation to its uptake, accumulation, and systemic bioavailability.Address for correspondence: Calvin C. Willhite, Risk Sciences International, 55 Metcalfe Street, Suite 700, Ottawa, ON, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
215
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(221 citation statements)
references
References 622 publications
(1,104 reference statements)
2
215
0
4
Order By: Relevance
“…The injected Al ADJ releases the biologically active form Al 3+ and aluminate (Al(OH) 4 − ) ions, which may react with water and finally lead to Al superoxide production [65]. However, most of the injected aluminium will be phagocytized and thereby activate cells that recruit even more inflammatory cells.…”
Section: Reviewmentioning
confidence: 99%
“…The injected Al ADJ releases the biologically active form Al 3+ and aluminate (Al(OH) 4 − ) ions, which may react with water and finally lead to Al superoxide production [65]. However, most of the injected aluminium will be phagocytized and thereby activate cells that recruit even more inflammatory cells.…”
Section: Reviewmentioning
confidence: 99%
“…Another systematic review on aluminum exposure from deodorant/antiperspirant use and breast cancer showed no clear evidence of an association. 55 Our analysis of online content found that 75% (n=27) of the webpages discussing aluminum exposure from deodorant use and breast cancer mentioned inconclusive or non-significant relationship between aluminum and breast cancer risk, while 25.0% (n=9) only focused on increased risk due to aluminum exposure.…”
Section: Discussionmentioning
confidence: 87%
“…Ek olarak, meme tümörünün meme içindeki yeriyle ya da evre, büyüklük ve steroid reseptörü durumu gibi tümörle alakalı diğer faktörlerle ilişkili olarak alüminyum konsantrasyonlarında anlamlı farklılıklar tespit edilmemiştir 30 . Alüminyum içeren koltuk altı antiperspirantlarının ya da kozmetiklerin meme kanseri riskini artırdığını gösteren açık bir kanıt bulunmamaktadır 31 .…”
Section: Introductionunclassified
“…Darbre 10 ve Harvey 12 , meme kanseri ile (paraben ve alüminyum içeren) koltuk altı kozmetiklerinin kullanımını doğrudan ele almaya yönelik iki epidemiyolojik çalışma bildirmişlerdir. Öte yandan diğer birçok çalışmada, meme kanseri riski ve antiperspirant kullanımı arasında ilişki bulunmamıştır 3,5,13,22,[24][25][26][27][28]30,31 . Meme kanseri hastaları ve etkilenmemiş kontroller arasında güncel antiperspirant/deodorant kullanımından kaynaklanan bir fark yoktur 28 .…”
Section: Introductionunclassified